The hard parts : a memoir of courage and triumph - Masters, Oksana, 1989-; Randall, Cassidy (Scribner, an imprint of Simon & Schuster, Inc., 2023)
The United States' most decorated winter Paralympic or Olympic athlete tells how she overcame Chernobyl disaster-caused physical challenges through sheer determination and a drive to succeed to win the world's best in elite rowing, biathlon, cross-countryskiing, and road cycling competitions.